Thin film rimming flow subject to droplet impact at the surface - Williams, Joanne, 1978- (2009)
A bearing chamber may be modelled as a horizontal cylinder, stationary or rotating about its axis, with a film of fluid coating the inside of the cylinder wall. The impact of droplets from a two-phase flow in the core of the chamber drives the motion of the oil film. In this thesis we develop a model for the film based on conservation of mass and momentum across the interface between the film and the core, droplet-laden flow.